Sosialisasi Pentingnya Sex Education Semenjak Dini - Pahrul, Yolanda; Saputra, Andri; Dewi, Mutiara; Salsabila, Sabina Naghama; Kusmiati, Kusmiati; Octaviani, Elma; Nurimah, Siti; Aeni, Siti Nurul; Hasanah, Uswatun; Ernawati, Sri (Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual education or sex education in early childhood is an important aspect in forming children's understanding of the body, personal boundaries, and the concepts of consent and safety. This education does not only focus on biological aspects, but also on ethical, social and emotional values that support children's healthy development. By providing age-appropriate information, children can better understand their bodies, recognize good and bad touch, and avoid the risk of sexual exploitation or violence. Not only that, the role of parents is also very important in looking after children in broadcasts on YouTube, television, in this case children often model what children have seen.